One Year Obstetric Experience with Extreme Complications in a Tertiary Center in Somalia - Erin, Recep; Ahmed, Zeina (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: The maternal mortality rate is very high in Sub-Saharan African countries with extreme complications not seen in developed countries. We aimed to analyze and compile data on obstetric emergencies and complications in a tertiary center in Somalia. Study Design: The files of all patients who visited the obstetrics clinic in Somalia Recep Tayyip Erdogan Training and Research Hospital between January 2018 and December 2018 were retrospectively scanned. All maternal demographic data, prenatal hemoglobin levels, serological markers, and complications were recorded. The correlation between the birth process and hemoglobin change was examined. Results: A total of 825 cases were identified. Overall, we found serious maternal complications: eclampsia, 12.4%; postpartum bleeding, 8.7%; placenta previa, 2.1%; placenta insertion anomalies, 1.4%; uterine rupture, 2.4%; and placental abruption, 2.5%. The mean hemoglobin value on admission was 10.39±1.74 g/dL. Further, the hemoglobin difference increased in low and high dilatation numbers. A low-level positive correlation was found between delivery time and the hemoglobin difference (r=0.23) and between delivery time and fetal complications (r=0.2). Conclusion: Postpartum bleeding and eclampsia were among the leading causes of maternal mortality in Somalia. In addition, insufficient surgical techniques and unsuitable environments increase maternal mortality.